2018
DOI: 10.1177/2325967118808782
|View full text |Cite
|
Sign up to set email alerts
|

Medial Elbow Pain During the Return-to-Throwing Period After Ulnar Collateral Ligament Reconstruction in Pitchers

Abstract: Background:Ulnar collateral ligament reconstruction (UCLR) is common in the sport of baseball, particularly among pitchers. Postoperative return-to-sport protocols have many players beginning to throw at 4 to 5 months and returning to full competition between 12 and 16 months after surgery. Medial elbow pain during the return-to-throwing period often occurs and can be difficult to manage.Purpose:To evaluate the incidence of medial elbow pain and associations with outcomes and revision surgery during the return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The shortest timeline for RTS documented among the 33 studies was 6.5 months, while the longest was 16 months. 3,34 A recent systematic review of 14 studies found that the mean time to RTS for baseball pitchers was 19.8 ± 13.5 months, and the mean time to return to competition for MLB pitchers was 17.3 ± 2.4 months. 16 Similar to the current study, Coughlin et al 15 found a large variation in the mean time to return to pitching (range, 11.5-20.5 months).…”
Section: Discussionmentioning
confidence: 99%
“…The shortest timeline for RTS documented among the 33 studies was 6.5 months, while the longest was 16 months. 3,34 A recent systematic review of 14 studies found that the mean time to RTS for baseball pitchers was 19.8 ± 13.5 months, and the mean time to return to competition for MLB pitchers was 17.3 ± 2.4 months. 16 Similar to the current study, Coughlin et al 15 found a large variation in the mean time to return to pitching (range, 11.5-20.5 months).…”
Section: Discussionmentioning
confidence: 99%
“…As the Ito method is similar to the Jobe and docking methods on the ulnar side and has been clinically proven to perform well in stability and load-to-failure biomechanical testing, we chose this technique to compare our novel anchor method with. 9 , 17 , 20 , 21 , 23 , 31 , 34 A 3.5-mm drill was used to create bone tunnels on the anterior and posterior aspects of the sublime tubercle, connected by a bone bridge of approximately 2 cm. The tunnels were created approximately 15 mm distal to the joint line.…”
Section: Methodsmentioning
confidence: 99%
“… 11 , 21 , 32 , 35 UCL reconstruction was first described by Jobe et al, 18 and various surgical methods have been reported to improve the rates at which athletes are able to return to play by as much as 78% to 91%. 4 , 10 , 20 , 23 , 32 Despite being a well-described technique, a number of postoperative complications have been reported, with ulnar nerve-related complications being especially interesting due to their poor clinical outcomes and need for further surgical procedures. 5 , 9 , 24 While the rate of ulnar nerve-related complications has decreased due to improvements in surgical methods, including selective transposition of the ulnar nerve and the muscle-splitting approach, 5 , 9 and despite having no effect on return to play, the incidence remains high, with complications occurring in 16% of cases (121 of 756 elbows) after UCL reconstruction by the modified Jobe method.…”
mentioning
confidence: 99%